2013
DOI: 10.1088/1468-6996/14/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of electrospun PCL/PMMA fibrous scaffolds for bone regeneration

Abstract: Scaffolds were fabricated by electrospinning using polycaprolactone (PCL) blended with poly(methyl methacrylate) (PMMA) in ratios of 10/0, 7/3, 5/5 and 3/7. The PCL/PMMA ratio affected the fiber diameter, contact angle, tensile strength and biological in vitro and in vivo properties of the scaffolds, and the 7/3 ratio resulted in a higher mechanical strength than 5/5 and 3/7. In vitro cytotoxicity and proliferation of MG-63 osteoblast cells on these blended scaffolds were examined by MTT assay, and it was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Several substances such as chitosan [83], PEI (polyethyleneimine) nanoparticles [84], 15% of N-acetyl cysteine (NAC) [87], calcium phosphate cement (CPC) [90], acrylic resin of different colors [91], (bone cement) enriched with microencapsulated 2-octyl cyanoacrylate (OCA), extracts solutions [92], scaffolds fabricated by electrospinning using polycaprolactone (PCL) [94], core/polyethyleneimine (PEI) shell magnetic nanoparticles [97], silver nanoparticles (AgNPs) [98], and Paladon 65-HR precoated with biosurfactant were also evaluated for cytotoxicity. The authors observed reduction in cytotoxicity and increase in biocompatibility from non-cytotoxic (cell viability higher than 75%) to slightly cytotoxic (cell viability ranging from 50 to 75%)…”
Section: Short-or Long-term Injection or Implantation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several substances such as chitosan [83], PEI (polyethyleneimine) nanoparticles [84], 15% of N-acetyl cysteine (NAC) [87], calcium phosphate cement (CPC) [90], acrylic resin of different colors [91], (bone cement) enriched with microencapsulated 2-octyl cyanoacrylate (OCA), extracts solutions [92], scaffolds fabricated by electrospinning using polycaprolactone (PCL) [94], core/polyethyleneimine (PEI) shell magnetic nanoparticles [97], silver nanoparticles (AgNPs) [98], and Paladon 65-HR precoated with biosurfactant were also evaluated for cytotoxicity. The authors observed reduction in cytotoxicity and increase in biocompatibility from non-cytotoxic (cell viability higher than 75%) to slightly cytotoxic (cell viability ranging from 50 to 75%)…”
Section: Short-or Long-term Injection or Implantation Studiesmentioning
confidence: 99%
“…Several studies have been carried out at short-or long-term implantation with PMMA enriched or coated with different materials as base bone cement-osteopal V modified with castor oil and linoleic acid in rats [86], coating with titanium dioxide (TiO 2 ) nanoparticles for hamster oral mucosa irritation and guinea pig skin sensitization and intracutaneous rabbit implantation [106], enriched with CPC in rats [90], scaffolds of electrospinning using polycaprolactone (PCL) implantation in rats [94], no toxic effect or histological findings were observed, even a regeneration was perceived. By contrast, the use of PMMA-PEI nanoparticles injected in mice induces significant toxicity by the detection of protein levels in liver tissue.…”
Section: Short-or Long-term Injection or Implantation Studiesmentioning
confidence: 99%
“…Poly methyl methacrylate (PMMA) is a commercially accessible bone cement with great mechanical characteristics, low toxicity, low cost, and ease of mass production. 1,2 PMMAbased bone cements are vital materials for orthopedic applications such as artificial joint fixations and also as filler for bone defects. However, PMMA suffers from a number of drawbacks which should be addressed before it is considered for orthopedic applications.…”
Section: Introductionmentioning
confidence: 99%
“…32,36 PMMA has oen been blended with PCL, a biodegradable, and mechanically robust material, [37][38][39][40] resulting in a composite system with increased thermal and mechanical stability. [41][42][43] Therefore, we developed PMMA/PCL electrospun ber mats, and we present herein their analysis regarding morphology, mechanical and wetting properties and, most importantly, oil absorption capacity and selectivity using a wide range of stabilized water in oil emulsions concentrations. The maximum oil absorption capacity reached is 25.3 g g À1 for the emulsions with 80 v% of oil, but with simultaneous absorption of a small amount of water.…”
Section: Introductionmentioning
confidence: 99%